The organizational alignment-strategy, structure and process: an empirical study regarding the Impact on the performances of military organizations - Pinto, J.; Altinsoy, N.; António, N. S. (Euro Asia Journal of Management, 2014)
This study focuses on the organizational alignment in terms of strategy, structure, process and their impacts on organizational performance through the utilization of Miles and Snow typology. It attempts to prove that attaining a fit between the organization and its target strategy contributes toward a better performance. Additionally, it tests the equifinality concept which expresses the idea that an organization can perform well with a variety of strategies. Based on the contribution of previous works, concerning the Miles and Snow typology and performance, this study should be seen as a replication regarding that issue, but here applied on the military industry. The study provides empirical support to the configurationally equifinality approach and fit the concept in the military environment. It also provides an alternative way to explain performance in this environment. To the best of our knowledge, no empirical studies exist where all these aspects were applied on military organizations.